Path Analysis on the Factors Affecting the Use of Personal Protection Equipment among Airport Construction Workers in Yogyakarta - Ristamaya Danar Dewi; Setyo Sri Rahardjo; Bhisma Murti (Journal of Health Promotion and Behavior, 2019)
Background: Occupational accidents in the construction sector are still a major problem in every infrastructure development in Indonesia. The lack of supervision in the use of personal protective equipment (PPE) is one reason for the high number of occupational accidents. This study aimed to determine the factors that influence the implementation of the use of PPE.Subjects and Method: A cross sectional study was conducted at Yogyakarta International Airport, Kulon Progo, Yogyakarta, Indonesia, in March 2019. A sample of 200 active field workers was selected by proportional random sampling. The dependent variable was the use of PPE. The independent variables were age, education, working experience, knowledge, perception of vulnerability, perceived benefit, perceived severity, and cues to action. The data were collected by questionnaire and analyzed by path analysis.Results: The use of PPE was directly and positively affected by high knowledge (b= 2.14; 95% CI= 1.17 to 3.10; p<0.001), high perceived susceptibility (b= 1.94; 95% CI= 0.95 to 2.93; p< 0.001), high perceived severity (b= 1.33; 95% CI= 0.42 to 2.24; p= 0.004), high perceived benefit (b= 1.79; 95% CI= 0.85 to 2.73; p<0.001), and high cues to action (b= 1.64; 95% CI= 0.67 to 2.61; p= 0.001). The use of PPE was indirectly affected by age, work experience, and education.Conclusion: The use of PPE is directly and positively affected by knowledge, perceived suscep¬tibility, perceived severity, perceived benefit, and cues to action. The use of personal protective equip¬ment is indirectly affected by age, work experience, and education.  Keywords: personal protective equipment, construction workers, path analysis Correspondence: Ristamaya Danar Dewi. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ristamayadd@gmail.com. Mobile: 082-131666953. Journal of Health Promotion and Behavior (2019), 4(1): 12-21https://doi.org/10.26911/thejhpb.2019.04.01.02